Antanas Smetona’s activities in the USA: Lithuanian-American mission and aspirations to restore the Lithuanian state - Banionis, Juozas (Genocidas ir rezistencija, 2020)
In describing the Lithuanian liberation movement that has formed in the West, the main political organizations of the Lithuanian diaspora (ALT), the Supreme Committee for the Liberation of Lithuania (VLIK), the Lithuanian Freedom Committee (LLK) and the Lithuanian Community of the World Lithuanian community are the most common. The merits of all of them, with their participation in the cause of Lithuanian freedom, are undeniable and sufficiently featured in Lithuanian history. However, in one way or another, the union (LVS) that emerged in the US as one of the first – back in 1941, when Lithuania had already lost its independence and its indiscriminate Sovietization was already taking place. Even later, in 1944, when circumstances changed and it became clear that the LVS was not able to form the global Lithuanian-American movement, the American Lithuanian Mission (ALM) appeared. The activities of the latter two organizations, expressing Lithuanian national unity, are closely related to President Ananas Smetona, who, after leaving for The USA, tried to bring together his compatriots in activities towards restoring Lithuania’s independence. It can be said that both the official State of the United States and A. Smetona himself, emphasizing that he was not the “property” of any single party, but still the constitutional president of Lithuania, had the hope of concentrating the Lithuanian diaspora on a united front for Lithuania’s liberation. He raised the desire of Lithuanians to restore the independence of the Fatherland and called for the association of state reformers, following the example of the creation of independence in 1918. However, the ambiguous attitude of Lithuanian political currents towards the person of President A. Smetona dissipated their ability to form a united front for the liberation of Lithuania. In spite of President A. Smetona emphasizing the important principle of continuance of the State of Lithuania and the basic credo formulated under the current conditions and the steps of the implementation of independence recognized by him, the possibility of achieving state sovereignty, the establishment of an existential government and the recognition that the people would continue to establish the order of the future of the state of its own will, the political opposition formed in the diaspora of the socialists and Catholic-clerics, which did not demonstrate the efforts to sacrifice the party interests in the name of unity for the State of Lithuania. The nationals, creating a counterweight to the emerging opposition-based Council of American Lithuanians (ALT), united and established the aforementioned LVS, the purpose of which was described as follows: to help Lithuania regain its freedom and restoration again as an independent state. Its activities, developed in two directions – between compatriots and Americans in society, included the dissemination of information (in writing and orally) about Lithuania, the expansion of the ranks of Lithuanian liberation participants or supporters, activation of support for the restoration of Lithuanian independence (Lithuanian national relief fund – Lithuanian National Relief Fund) was established under the auspices of the organization. Thus, LVS, recognizing the ideological leadership of the Republic of Lithuania in President A. Smetona, undertook to act until a free and independent state was restored. In the belief of western democracy, the President of Lithuania took the position that, under Soviet or Nazi occupation, the bodies of the powers formed by those regimes would not be recognized in Lithuania. This belief was further strengthened when the US and Great Britain proclaimed the Atlantic Charter, declaring the principles of the new world order at the end of the war. While the changing international circumstances (the alliance formed in the West, which unites the Alliance against Hitler’s Germany), began to stop Lithuania’s liberation, President Smetona, in accordance with the established right of the Atlantic Charter to choose the preferred form of governance, underlined this fundamental law of democracy that would guarantee the sovereignty of the nation. In addition, the President had clearly described and restored the political direction of the State of Lithuania: “Our attitude should be directed only at a democratic Europe, in no way to the East.” The unity sought by the President, based not on party principles, but on the common engagement of people from different political currents in the matter of Lithuanian freedom, was not achieved in 1943 to commemorate the 25th anniversary of Independence. Following the example of the Universal Lithuanian Parliament held in New York on 13-14 March 1918, LVS, having assessed the international situation in early 1944 and comparing it to the events of the time, held the Lithuanian- American Parliament in New York on 5-6 February 1944. In addition to the participation of Lithuanian President A. Smetona, it was expected to elect a Lithuanian-American delegation, which should clarify the US position on the prospect of Freedom and Independence of Lithuania. But with the unexpected change in circumstances (the death of President A. Smetona), the work of the Parliament was adjusted and adopted a resolution still calling for the connection of all Lithuanian-Americans into the joint liberation of Lithuania. However, in the run-up to the end of the war in Europe and complicating the fate of the Baltic states, LVS abandoned the idea of a Common Lithuanian parliament and decided rather to represent the national emigrant line of reasoning, creating a narrower-scale entity – the American Lithuanian Mission (ALM). It was a new form of expression based on the concept of mission, i.e. “the move to American society”. On March 23-24, 1945, Lithuanian-Americans prepared events that made the name of Lithuania known, while raising the issue of freedom. Those events (attending the White House, meeting at dinner) included the political and societal circles of the US, for which the expectations of Lithuanians were expressed in becoming a free and independent nation. Another sign of ALM’s ordeal in promoting the issue of Lithuanian freedom was in May 1945, when the inaugural United Nations (UN) conference was held in San Francisco. It requested the inclusion of a paragraph into the new UN declaration where an independent Republic of Lithuania should become a member of the UN and participate lawfully in the activities of the organization. After the end of the war in Europe, there followed the hostilities in Japan without any changes in the international framework to restore Lithuania’s independence, ALM continued its liberation campaign by making an appeal to the President of the United States by visiting the State Department. However, in the context of the current political reality, as the freedom of Lithuania together with the other two Baltic countries continued to do so, the nationalists began to adjust their freedom efforts, gradually moving to raising the nearest, smaller, but relevant issues for the Lithuanian people (Lithuanian emigration to US Affairs, Lithuanian Day – February 16th promotion, etc.). Another significant step in the formation of the Lithuanian Liberation Movement in the West was the 1948 LVSALM consolidating into ALT, which thus brought together all four patriotic Lithuanian political currents – Catholics, covenanters, socialists and nationalists, making their liberation activities more effective and, hopefully, consolidating the views of US politicians and society on the rise of Lithuanian freedom.